Knowledge With The Attitude Of Acceptance Of The Covid-19 Vaccine In Tuminting Subject, Manado City - Faradilla Miftah Suranata; Rahmat Hidayat Djalil; Julfiani Sampurna (Science Midwifery, 2022)
Coronavirus Disease 2019 (Covid-19) is an acute respiratory infection that occurs in droplets containing SARS-CoV-2 so that it enters the body and can be prevented by vaccination. Vaccines are one of the most effective and economical ways to prevent infectious diseases, especially Covid-19. The attitude of accepting the Covid-19 vaccine is a response or acceptance of information as well as a response to the response of whether the community wants to accept vaccination or not. Vaccination will be able to run well and achieve goals evenly if the entire community can accept the Covid-19 vaccination. The purpose of this study is to identify the relationship with the attitude of acceptance in society. The design of this research is descriptive analytical with a cross sectional approach. The sample of this research is the community of Tuminting Environment II Village, Manado City, totaling 40 respondents using the Accidental Sampling Technique. This research instrument was conducted using a questionnaire. Furthermore, it was analyzed by Chi-Square statistical test with a significance level of = 0.05. The results of the study showed poor knowledge 26 (65%), attitude of acceptance who received less vaccination 22 (55%) and the results of the analysis test obtained p value of 0.001. The conclusion in this study is that there is a significant relationship between knowledge and attitudes towards receiving the Covid-19 vaccine in the community of Tuminting Environment II Village, Manado City. Suggestions in this study are that it is hoped that the community can increase existing knowledge in order to deepen knowledge in order to apply a good acceptance attitude.